Comprehensive assessment of the urban ecosystem ecological state of the city of Slutsk - Mazets, Zhanna; Bonina, Tatsiana; Prakhotskaya, Nadezhda (Journal of the Belarusian State University. Ecology, 2023)
The results of a comprehensive assessment of the Slutsk urban ecosystem ecological state have been discussed in the article. The analysis of the recreational disturbance degree and the grade of green planting’s resistance in the urban environment with different levels of anthropogenic load was carried out: in the suburban area (control), the central zone of the Park of Culture and Recreation and in the territory with a high anthropogenic load of the environment, which is located near industrial enterprises of Slutsk city. A low degree of recreational disturbance has been established in the control and in the park zone, while in the zone of industrial enterprises the state of the environment was assessed as threatening. A speciesspecific reaction of morphometric changes in the leaf blades of Betula pendula Roth and Tilia cordata Mill. has been revealed using the fluctuating asymmetry method, which reflects the features of the individual components ecological state of the urban ecosystem. It was noted that the tree stand of the Park of Culture and Leisure is in a satisfactory condition and is functional as a sanitary protection zone in an urban environment. However, at the site located near industrial enterprises, the state of bioindicators is assessed as critical and suggests that in this area there is a rather high level of environmental pollution with harmful substances. In the course of a detailed study of species-specific differences in the morphometric parameters of Betula pendula and Tilia cordata, it has been revealed that the most variable indicator was the angle between the main vein and the second-order vein from the base of the leaf. It is here that there are clear specific differences between Betula pendula and Tilia cordata. Thus according to this indicator Betula pendula had an average level in the control and increased in the conditions of the park and the industrial zone (up to level IV), while Tilia cordata had the lowest level in the control, and with an increase in anthropogenic load it reached critical values and a maximum was in the industrial zone. It is noted that it is expedient to develop a relative integral indicator of fluctuating asymmetry in comparison with the control for a certain plant species. Thus, Tilia cordata can be considered as an effective bioindicator of the urban ecosystems’ state. The obtained results make it possible to recommend the environmental services of the Slutsk city to reconsider approaches to greening the area around industrial enterprises, considering the growing anthropogenic load.
Keywords: Betula pendula Roth; Tilia cordata Mill; fluctuating asymmetry; degree of plantation degradation